A Fundamental Solution of N. Zeilon's Operator - Wagner, Peter (Mathematica Scandinavica, 2000)
In this paper, we resume earlier work of N. Zeilon and of J. Fehrman and derive an explicit re- presentation by elliptic integrals of a fundamental solution of the partial differential operator $\partial_1^3+\partial_2^3+\partial_3^3$.